STRUCTURAL ANALYSIS OF ACRIDINEDIONES AND CONDENSED ACRIDINES DERIVATIVES BY MASS SPECTROMETRY - PERIYASAMY MURUGAN (International Journal of Pharma and Bio Sciences, 2015)
Several series of acridinediones and pyrazoloacridines derivatives have been investigated by EI mass spectrometry because of their versatile wide applications such as laser dyes1, OLED properties2,solar cell3and biological activities4. For all acridinediones compounds the electron ionization (EI) spectra are very clean, being dominated by loss of atoms or radicals such as CO,CH3, ketene, isobutylene. In the case of pyazoloacridine derivatives, loss of H and HCN was observed from the compounds derived from dihydroresorcinol and loss of H, CH3 due to presence of methyl groups was observed from the compounds derived from dimedone. In this paper, we would like to report the mass spectral fragmentation of 9- mono substituted acridinediones(1a-g , 2a-h) and 10,10Ê¹-bisacridinediones (3a-c), 9,9Ê¹- bisacridinediones(4a-b) and mono,bis-pyrazoloacridine derivatives (5 a-d,6 e-g,7).